The Content And Principles Of The Social-Pedagogical Approach In Family Upbringing - Saitova Muattar (Next Scientists International Journal JSSHRF, 2026)
Family upbringing remains the primary environment where a child’s worldview, social behavior, and value orientations are formed. Contemporary social change, digitalization, migration, economic instability, and increasing diversity of family structures have complicated this process and expanded the range of risks for children’s development. In this context, the social-pedagogical approach offers a coherent framework for understanding family upbringing not only as a private matter, but also as a socially conditioned pedagogical reality that can be supported through professional guidance, community resources, and preventive interventions. Using theoretical analysis and model-based synthesis, the study clarifies the approach’s conceptual foundations, its key functions in the family context, and the guiding principles that ensure ethical, culturally responsive, and developmentally appropriate practice. The results formulate a principle-based framework that integrates child-centeredness, systemicity, partnership, inclusion, preventive orientation, continuity, and reflective support. The discussion highlights how these principles translate into real family interactions and professional activities, emphasizing the balance between parental autonomy and social responsibility. The article concludes that the social-pedagogical approach strengthens family upbringing by connecting family resources with institutional support while protecting the child’s rights and promoting resilience.